Citizen science: expanding ideas of citizenship and science. Issue 1 (25th April 2020) - Kenyon, Elizabeth; Christoff, Andrea; Wisdom, Sonya
Abstract : Purpose: This action research project determines the extent to which the authors were able to expand ideas of both citizen and scientist through their integrated science and social studies middle childhood methods course. Design/methodology/approach: Applying the ideas of citizen science, students in the course developed inquiry projects of their choice centering on the topic of local and global water issues. In addition, students participated in book groups focusing on the ideas of citizen science explicitly. The researchers used surveys, student assessments and interviews to assess the extent to which students' ideas changed. Findings: While the data reveal the students' conceptions of scientist and citizen both expanded, there was greater change in their conceptions of what it means to be a scientist. Originality/value: The authors argue that the expansion of ideas of science is important for enacting critical citizenship.